1972
DOI: 10.1126/science.178.4067.1288
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Cancer in vivo by Nuclear Magnetic Resonance

Abstract: Pulsed nuclear magnetic resonance has been used to differentiate in vivo between normal mouse tail tissue and a malignant transplanted melanoma, S91, located on the tail. The tumor displayed a nuclear (proton) spin-lattice relaxation time of approximately 0.7 second contrasted with the simultaneously measured normal tail tissue relaxation time of approximately 0.3 second.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1
1

Year Published

1974
1974
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(36 citation statements)
references
References 4 publications
1
33
1
1
Order By: Relevance
“…The study was subsequently confirmed at a higher frequency (100 MHz) by lijima and Fujii (2), by Hazlewood et al (3) who added NMR measurements of the diffusion coefficient of water for tumor tissues, in the tail of a live animal by Weisman et al (4), and in single cells transformed in vitro by Carver (5).…”
mentioning
confidence: 60%
“…The study was subsequently confirmed at a higher frequency (100 MHz) by lijima and Fujii (2), by Hazlewood et al (3) who added NMR measurements of the diffusion coefficient of water for tumor tissues, in the tail of a live animal by Weisman et al (4), and in single cells transformed in vitro by Carver (5).…”
mentioning
confidence: 60%
“…The first nuclear magnetic resonance images were produced by Lauterbur in 1973 (25) using a modified, conventional NMR spectrometer. The potential application of this technology to medical diagnosis was immediately apparent, since it had already been noted that NMR parameters [specifically, the proton (H-l) relaxation times T 1 and T 2 ] appeared to be altered in tumors when compared to corresponding normal tissues (26,27). In the ensuing years, advances in methods and instrumentation have resulted in the development of large scale NMR imaging devices which are now being used in clinical trials worldwide (28,29).…”
Section: Thank Youmentioning
confidence: 99%
“…Since as early as 1959, when Singer utilized NMR to assess blood flow rates in the tail of a mouse (17), the mouse has played an important role in the development of many pioneering accomplishments in both MRI and MRS (18)(19)(20)(21)(22)(23)(24). With the advent of genetic engineering, this small animal has itself become the center of interest, and dedicated MR technologies have been adapted to help study and better understand the proliferation of mouse models of human diseases.…”
Section: Mr Of Transgenic Micementioning
confidence: 99%